Pengaruh Pekerjaan Pendapatan Dan Pendidikan Orangtua Terhadap Penderita Pufa - Kevin Imanuel Tarigan; Molek Molek; Mangatas Halomoan Parluhutan Hutagalung (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Many dental health problems occur in school-age children is dental caries. If dental caries untreated it’s will be continued to dentin layers and pulp, that causing pulp involvement (P/p), ulceration (U/u), fistula (F/f) and abscess (A/a).The role of parents is needed to supporting the health of their children oral cavity. The role of parents to protect the health of children oral cavity can be affected by work, income and education of parents. Research Objectives: to observe the effect of work, income and education of parents on patient with PUFA/pufa at SD Negeri 065012 Medan Tuntungan District, Medan city. Type of this research is analytic cross sectional. Determination of the sample using purposive sampling. PUFA/pufa assessment based on index PUFA/pufa. Data analysis Bivariate with the Chi-Square Test analysis technique. Results the research shows respondent’s the effect of the parents work is obtained value p=0,000, respondent's the effect of parent's income is obtained value p=0,000 and respondent's the effect of the parental education is obtained p=0,000. Conclusion: there is an effect of work, income, and education of parents on patient with PUFA/pufa it shows significant value of p=0,000 (p <0.05).